Cognitive reserve over the life course and risk of dementia: a systematic review and meta-analysis - Liu, Yulu; Lu, Guangyu; Liu, Lin; He, Yuhang; Gong, Weijuan (Frontiers in Aging Neuroscience, 2024)
Background: The number of people with dementia is soaring. Cognitive reserve has been thought to be associated with dementia risk. It is not clear at which period in the life course and which cognitive reserve proxies contribute to the reduced risk of dementia. Methods: By scanning four databases (PubMed, Embase, Web of Science, and MEDLINE) up to Jun 3, 2023, longitudinal studies of life-course cognitive reserve and risk of dementia were found. The HRs and 95% CIs for each study were summarized using random effects models. Subgroup analyses and sensitivity analyses were conducted. Utilizing funnel plots, Begg and Egger tests, publication bias was investigated. Results: A total of 27 studies were included, containing 10 in early-life, 10 in middle-life, and 13 in late-life. All studies used validated questionnaires to measure cognitive reserve, and dementia diagnosis followed recognized worldwide guidelines. All included studies were of medium or low risk. Cognitive reserve in early-life (Hazard ratio (HR): 0.82; 95% confidence interval (CI): 0.79-0.86), middle-life (HR: 0.91; 95% CI: 0.84-0.98) and late-life (HR: 0.81; 95% CI: 0.75-0.88) all have protective effects on dementia risk. Multiple sensitivity analyses showed consistent results. Conclusions: Dementia risk is reduced by the buildup of cognitive reserves during life-course. Accumulation of proxies for cognitive reserve in early and late life had the greatest effect on dementia risk reduction. Social connection may be an effective approach to lower dementia risk.